Digital Literacy of Tuntungan I Village Youth In Utilizing Social Media As Learning Media - Ramadhana, Tri Wahyu; Ahyar, Juni; Iqbal, Muhammad; Safriandi, Safriandi (Asian Journal of Social and Humanities, 2024)
This research is a qualitative study which aims to measure the level of awareness of teenagers in Tuntungan I village regarding the importance of digital literacy in utilizing social media as a learning medium, and to analyze teenagers' dependence on social media which can influence the effectiveness of learning. The research was carried out from 03 to 13 June 2024 in Tuntungan I Village, Pancur Batu District, Deli Serdang Regency, North Sumatra. Data collection techniques use interview techniques and questionnaires. The number of samples taken was 30 teenagers who were classified based on their age level. The research results obtained were that teenagers in Tuntungan I Village had demonstrated proficiency in using digital media, such as PowerPoint and Infocus, to present discussion results. This reflects their skills in supporting technology as an important learning tool in the school environment. The social media platforms that are often used by teenagers in Tuntungan I Village to search for information are YouTube and Instagram. The information seeking skills of teenagers in Tuntungan I village show significant dependence on social media as a source of information. From the results of calculations with respondents, 87.3% of teenagers actively use this platform for the purpose of seeking information. However, only 60.7% succeeded in finding information that was relevant to their learning.